PENGARUH LINGKUNGAN KERJA FISIK DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN PADA PT INFRASTRUKTUR TELEKOMUNIKASI INDONESIA - Nadya Nurul Fitri; Ary Ferdian (Departemen Manajemen, 2021)
This study is aime at finding the effect physial work environment and non physical work environment on employee performance at PT Infrastruktur Telekomunikasi Indonesia, either simultaneously or partially. The purpose of this research is to find out how and how much influence the physical work environment and non-physical work environment have on the performance of the employees of PT Infrrastruktur Telekomunikasi Indonesia. Quantitative methods with data collection techniques using a questionnaire distributed to 119 employees of PT Telkominfra. In this study using descriptive analysis techniques and multiple linear analysis, with hypothesis testing using the T test, F test, and the coefficient of determination. Data processing shows the results that the physical work environment and non-physical work environment partially and simultaneously affect the performance of employees of PT Infrastruktur Telekomunikasi Indonesia. Based on the results of the coefficient of determination, it was found that the physical work environment and non-physical work environment had an effect on the performance of the employees of PT Infrastruktur Telekomunikasi Indonesia by 33.06% and the remaining 66.94% was influenced by other variables.